The Utilization of the Blooket Application to Enhance the Learning of Akidah Akhlak Subject at Junior High School - Khanah, Dewi; Alam, Naufal Ahmad Rijalul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This research aims to assess the effectiveness of using the Blooket application in enhancing Akidah Akhlak learning at SMP Muhammadiyah Kasihan. A descriptive qualitative approach was employed by using primary and secondary data sources. Primary data is obtained from interviews and observations, while secondary data is collected through documentation. The data was collected through interviews and questionnaires involving Akidah Akhlak teachers and 7th-grade students around 25 students. The analysis process included data reduction, presentation, and verification. The study found that before using Blooket, learning relied on traditional, less engaging methods, leading to low student participation. After implementing Blooket, student motivation and involvement increased significantly. All students found Blooket accessible, 96% considered it effective for learning, and 92% found it more engaging. The app's strength lies in its gamification features, making learning enjoyable and competitive. Gamification tools like Blooket offer an innovative approach to enhancing Akidah Akhlak education in the digital era.